EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN LOWCOST DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF PADA MATERI USAHA, ENERGI DAN PESAWAT SEDERHANA SISWA SMP NEGERI 2 TAMBANG - Tanjung, Azzahra Faudie; Z, Fakhruddin; Irawan, Dedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student learning outcomes are caused by many factors, one of which is inadequate laboratories and inappropriate use of learning media chosen by teachers. One solution that can be done due to the lack of learning media is to utilize simple materials and tools available in the surrounding environment that can be used in learning during practicums. The purpose of this study is to examine the effectiveness of using low-cost learning media in improving students' cognitive learning outcomes. The type of research used is a quasi-experimental study with a post-test only control group design. The research sample was taken from two classes using random sampling techniques as the experimental class and the control class from the population of class VIII IPA SMPN 2 Tambang students. The data collection instrument used was a post-test of cognitive learning outcomes in the form of 20 objective questions. Data were analyzed using descriptive and inferential analysis. The results of the descriptive analysis obtained that the average achievement of cognitive learning outcomes of class VIII.7 students as the experimental class was 57.83 with a fairly good category, while the average achievement of cognitive learning outcomes of class VIII.6 as the control class was 49.50 with a fairly good category. The results of the inferential analysis using the independent-sample t-test showed that there was a significant difference in students' cognitive learning outcomes between the experimental class and the control class, so that learning using low-cost learning media was effective in improving students' cognitive learning outcomes, especially in the material on work, energy and simple machines.